DESIGN AND SIMULATE IMPROVED PSRR IN A LOW DROPOUT VOLTAGE REGULATED WITH AN AC COUPLED SHUNT REGULATION TECHNIQUE - Paulo, Bruno Miguel Mateus (2023)
The focus of this thesis is to explore a solution that improves the PSRR at medium frequencies, specifically, between 10 MHz and 50 MHz, without significantly increasing the circuit area. To achieve this objective, a Shunt Regulator was designed to be implemented after the LDO. This device has the advantage of being able to be activated or deactivated without affecting the operation of the LDO. To improve the PSRR, the Shunt Regulator always consumes an output current pre-defined by the designer, which can be readjusted. When the LDO output voltage is higher than the desired voltage, the Shunt Regulator increases current consumption to reduce this voltage; conversely, when the LDO output voltage is below the desired level, the Shunt Regulator reduces the power consumption current to increase the output voltage of the LDO. The experimental results reveal a PSRR improvement of at least 6 dB when the preset current by the Regulator shunt consumes 10% of the LDO output current and an improvement of at least 8 dB when the preset current by the shunt regulator consumes 20% of the LDO output current under scientific PVT conditions.